Complete genome sequences and comparative secretomic analysis for the industrially cultivated edible mushroom Lyophyllum decastes reveals insights on evolution and lignocellulose degradation potential - Xu, Lili; Yang, Wujie; Qiu, Tianmei; Gao, Xia; Zhang, Hongyong; Zhang, Shuliang; Cui, Hui; Guo, Lizhong; Yu, Hailong; Yu, Hao (Frontiers in Microbiology, 2023)
Lyophyllum decastes, also known as Luronggu in China, is a culinary edible and medicinal mushroom that was widely cultivated in China in recent years. In the present study, the complete high-quality genome of two mating compatible L. decastes strain was sequenced. The L. decastes LRG-d1-1 genome consists of 47.7 Mb in 15 contigs with a contig N90 of 2.08 Mb and 14,499 predicted gene models. Phylogenetic analysis revealed that L. decastes exhibits a close evolutionary relationship to the Termitomyces and Hypsizygus genus and was diverged from H. marmoreus 45.53 Mya ago. Mating A loci of L. decastes compose of five and four HD genes in two monokaryotic strains respectively. Mating B loci compose of five STE genes in both two monokaryotic strains. To accelerate the cross-breeding process, we designed four pairs of specific primers and successfully detected both mating types in L. decastes. As a wood-rotting mushroom, a total of 541 genes accounting for 577 CAZymes were identified in the genome of L. decastes. Proteomic analysis revealed that 1,071 proteins including 182 CAZymes and 258 secreted enzymes were identified from four groups (PDB, PDB+bran, PDB+cotton hull, and PDB+sawdust). Two laccases and a quinone reductase were strongly overproduced in lignin-rich cultures, and the laccases were among the top-3 secreted proteins, suggesting an important role in the synergistic decomposition of lignin. These results revealed the robustness of the lignocellulose degradation capacity of L .decastes. This is the first study to provide insights into the evolution and lignocellulose degradation of L. decastes.